Сказки из леса - Юдаева Марина Владимировна (Школьная библиотека, 2014)
Экземпляры: СФ-2 (20150717) / Инвентарный номер: 38494z2 / Цена: 87.00 / Сис.шифр: 84(2) / Авт.знак: С 42 / ГРНТИ: 17.82.93 / ББК: 84(2=Рус)